Treatment of hepatocellular carcinoma with sorafenib: focus on special populations and adverse event - Schott, Eckart; Ebert, Matthias; Trojanek, Joanna B. (Zeitschrift für Gastroenterologie, 2012)
Sorafenib, a receptor tyrosine kinase-inhibitor with anti-proliferative and anti-angiogenic activity, is currently the only approved systemic treatment for patients with hepatocellular carcinoma. It inhibits downstream signaling of VEGFR-2, PDGFR, c-Kit receptors and BRAF. Over the last four years comprehensive experience with sorafenib in this indication has been accumulated. In this review we discuss the current data on the use of sorafenib in patients with advanced HCC including special patient populations such as patients with impaired liver function, patients after transplantation, and others. The most frequent side-effects and practical tips on how to manage them are discussed in detail. In addition, we summarize the current experimental data on the use of sorafenib in combination treatment, e. g., together with transarterial chemoembolisation or other targeted agents.